PIERRE BOURDIEU DAN KONSEP DASAR KEKERASAN SIMBOLIK - Nur Ika Fatmawati; Ahmad Sholikin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2020)
Symbolic violence is indeed not a form of violence that is easily seen, but actually this form of violence is very easily observed. It is actually everywhere, in the world of education, with its various forms and strategies. This concept was put forward by Bourdieu, a sociologist from France. Bourdieu uses this concept to explain the mechanism used by elite groups or upper groups that dominate the social structure of society to 'impose' ideology, culture, habits, or lifestyle on the lower class who dominate it. This cultural series by Bourdieu is also called habitus.